Commentary on the What Works Clearinghouse Standards and Procedures Handbook (v. 4.1) for the Review of Single-Case Research. (December 2022) - Maggin, Daniel M.; Barton, Erin; Reichow, Brian; Lane, Kathleen Lynne; Shogren, Karrie A.
The What Works Clearinghouse (WWC) provides school personnel with information on the amount and quality of evidence for educational programs, policies, and interventions. Over a decade ago, the WWC expanded their review procedures to include single-case research methods. Originally included as pilot standards, the recent updates elevated single-case research to a more prominent role for informing the development of evidence reviews and practice guides. While we applaud the removal of the pilot designation, our review of the updated procedures revealed concerns that, in our estimation, systematically favor studies based on nonexperimental criteria and inadequately address many issues and challenges with single-case research methods while overlooking other important concerns. As such, we are concerned that the current procedures will reduce the quality of information drawn from single-case research and disseminated to school personnel. In the following commentary, we describe these concerns and provide solutions-based recommendations for strengthening the standards and review process.